Wales. (UK : Foreign and Commonwealth Office, 1996)
History, people, country, administration, economy, environment, social welfare, culture and recreation in Wales.
Keywords: Wales; British geography; Wales (Great Britain) -- Geography; Wales (Great Britain) -- Geography